Treatment outcome and long-term stability of class II correction with forsus fatigue resistant device in non-growing patients - ACAR, YASEMİN BAHAR (WILEY, 2021)
Objectives Forsus (TM) Fatigue Resistant Device (FRD) is one of the commonly used semirigid fixed functional devices. Purpose of the present study was to investigate effects and long-term stability of Class II correction following use of Forsus FRD in a retrospective clinical study. Setting and Sample Population Records of 20 patients (mean age 18.3 +/- 2.5 years) with Class II malocclusion, who had undergone fixed functional treatment protocol with Forsus FRD, were collected from our clinical archive. Materials and Methods Lateral cephalometric radiographs at pre-treatment (T0), end of comprehensive treatment (T1) and post-retention period (T2, mean duration: 19 +/- 3 months) were analysed and superimposed to assess skeletal and dental changes on the long-term. Repeated measurement one way ANOVA was used for the study of the significant differences among the mean values of cephalometric parameters at T0, T1, and T2. To analyse the nature of the bilateral significant differences between two different time points, Bonferroni test was used. Results Sagittal and vertical skeletal changes at T0-T1 were statistically insignificant while all dentoalveolar parameters exhibited highly significant changes. At T1-T2, all skeletal and dentoalveolar parameters were stable except the slight relapse in overjet (0.3 +/- 0.5 mm;P < .05). At T0-T2 interval, no significant skeletal changes were recorded while the dentoalveolar changes remained significantly improved. Conclusion Correction of Class II malocclusion achieved with Forsus FRD was dentoalveolar and treatment effects were stable in the 19 +/- 3 months follow-up period.
Keywords: class II malocclusion; fixed functional devices; forsus fatigue resistant device; JASPER-JUMPER; MALOCCLUSION; APPLIANCE; PREVALENCE; ELASTICS